Generalized mathematical model of air outflow from compartment - Доник, В. Д. (Proceedings of National Aviation University, 2021)
Has been developed the generalized mathematical model of air outflow from compartment, examined the special cases and ranges of application. Have been carried out the comparisons of calculations results for model and experiment. The developed mathematical model describes with adequate for practice accuracy the process of air pressure variation in compartment.